2013
DOI: 10.5897/ajps2013.1027
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antifungal effects of the essential oil of Mentha piperita L. and its comparison with synthetic menthol on Aspergillus niger

Abstract: The antifungal activity of Mentha piperita L. essential oil and its comparison with synthetic menthol on Aspergillus niger growth have been determined in vitro. The chemical compositions of essential oil of M. piperita provided from the aerial parts of plants grown in a village in Kerman Province in June 2012 were determined. The sample was cleaned and then dried in the shade. Essential oil was made by hydro-distillation method and analyzed by capillary gas chromatography (GC) using flame ionization (FID) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
27
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 22 publications
7
27
0
3
Order By: Relevance
“…Based on the aforementioned studies, the antifungal activity of the plants attributed to the various kinds of secondary metabolites like flavonoids, alkaloids, phenolic acids and the essential oils 34,35 . S. obtusifolia aqueous extract A. niger [28] Antifungal activity of the tested plants in the present study also can be attributed to the various polar phytochemicals in their aqueous extracts.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…Based on the aforementioned studies, the antifungal activity of the plants attributed to the various kinds of secondary metabolites like flavonoids, alkaloids, phenolic acids and the essential oils 34,35 . S. obtusifolia aqueous extract A. niger [28] Antifungal activity of the tested plants in the present study also can be attributed to the various polar phytochemicals in their aqueous extracts.…”
Section: Resultsmentioning
confidence: 66%
“…The results indicated that the oil of M. piperita inhibits growth of all tested fungus species 27 . Menthol, the main organic component of M. piperita oil, effectively contributed to high antifungal activity of the oil 28 . In addition, oil of M. pulegium, which was reach in puelgone, had great potential for antibacterial and antifungal activities against tested microorganisms including A. niger and A. flavus 29 .…”
Section: Introductionmentioning
confidence: 99%
“…The results of Iscan et al (2002) showed that menthone was less active than menthol against C. albicans. In a study by Moghtader (2013), peppermint oil at 1 and 0.5 dilutions exhibited stronger antifungal effect than gentamycin or synthetic menthol.…”
Section: The Antifungal Properties Of Peppermint and Thyme Essential mentioning
confidence: 97%
“…The basic form of menthol present in nature is (−)menthol. Investigations confirmed that this compound has local anesthetic and counter irritant intimacy, and it is broadly applied to relieve minor throat irritation (Moghtader 2013). …”
Section: Effect Of Nacl and Iron Nanoparticles On Mentha Piperita Essmentioning
confidence: 99%